2011
DOI: 10.1111/j.1440-1827.2010.02634.x
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of the B‐cell receptor signaling component CD79b in plasma cell myeloma: A possible post transcriptional regulation

Abstract: The CD79 molecule, encoded by the CD79a and CD79b genes, is a signaling unit of the B-cell receptor complex, which transmits signals of B-cell activation, growth, and differentiation. They are B-cell-specific and expressed at most stages of B-cell development. Although plasma cells have been believed to lack these gene products, the regulation of CD79 expression in plasma cells is still controversial. In particular, the regulation of CD79b expression remains unclear. We sought to examine CD79b expression in no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 26 publications
1
12
0
Order By: Relevance
“…2c ). These results are consistent with the previous histological analysis of human lymph nodes reported by others 17 , strongly suggesting that expression of Igα and Igβ are differentially regulated in GC B cells.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…2c ). These results are consistent with the previous histological analysis of human lymph nodes reported by others 17 , strongly suggesting that expression of Igα and Igβ are differentially regulated in GC B cells.…”
Section: Resultssupporting
confidence: 93%
“…Antigen receptors of GC B cells are believed to be cross-linked by the cognate antigen during positive selection, which may result in the internalization of the BCR with its associating molecules, including Igα and Igβ. Thus, in addition to transcriptional regulation, we cannot completely rule out the possibility that post-translational modulation such as internalization, circulation or degradation of Igβ in association with BCRs may also be involved in its down-regulation 15 16 17 41 42 . Indeed, existence of an as-yet-unknown mechanism for post-transcriptional modulation of Igβ expression, which differ from Igα, was suggested in human GC B cells 17 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although little is known about the exact function of IGKV1-5, it has been shown that it is expressed in leukocytes in human peripheral blood,38 and that various types of cancer cells effect significant reduction of the expression of immune-response related genes, such as those involved in antigen presentation pathway,39 genes in the B-cell receptor complex,40 genes in the human leukocyte antigen (HLA) class,41 etc. More specifically, in connection with breast cancer, it has been observed that significant down-regulation of immune-response related genes was significantly associated with tumor progression, nodal involvement, lymphatic invasion, and risk of breast cancer reccurence 41.…”
Section: Resultsmentioning
confidence: 99%
“…The engaged BCR triggers phosphorylation of these subunits with the subsequent triggering of clonal B cell expansion and production of secreted immunoglobulin (2). The expression of the BCR is repressed during the terminal stages of B cell differentiation, and the CD79b/CD79a encoded proteins are undetectable in terminally differentiated plasma cells (3,4). Abnormal expression of CD79b has been associated with a variety of B cell malignancies (5,6), including chronic lymphocytic leukemia (7,8).…”
mentioning
confidence: 99%